The Government's Role in the Protection and Management of the Environment in the Kalimas River, Surabaya - Habibi, Miftakhur Rokhman; Salam, Mohammad Alfi F Z (International Journal of Law Dynamics Review, 2023)
The government's efforts to maintain the balance of the environment in development and natural preservation are unending. This research uses a combined type of legal research between normative and empirical juridical approaches (Mixed Method). The government issued a legal product in Law No. 32 of 2009 concerning the Protection and Management of the Environment to achieve this goal. The conclusion is the formation of the basis of human ethics for the environment has a major influence in creating and shaping the environment in the future for generations to come to create a healthy and clean-living environment to be used as a place for human habitation. It can avoid some unwanted things such as bad impacts and other environmental damage that can be detrimental to the state and harm everyone who lives around the damaged environment. It is important to involve several parties in environmental management such as the government and the community.